The contradictions of democracy in Afghanistan: elites, elections and 'people's rule' post-2001. Issue 6 (1st November 2016) - Schmeidl, Susanne
Abstract: The limited progress of democratisation in Afghanistan is examined in this article through the lens of elite-versus-citizen analysis. It challenges a culturalist explanation that suggests limited experience with democracy as well as religious and cultural values can hamper democratisation. Instead, it proposes a political-institutional rationale that presents two key arguments about the problems with democratisation in Afghanistan. First, there was a fundamental mismatch between the new institutions developed under the auspices of the US and international community and local conditions. Second, Afghan elites managed to manipulate these new institutions in their struggle for power, creating 'negative hybridity' in the form of neo-patrimonialism. The result is a widening gap between Afghan citizens and elites, and by extension the international community that is seen as colluding with local elites under the guise of democracy assistance. The future of democracy in Afghanistan depends on elites catching up with the Afghan population in embracing democracy for what it is—the rule of the people.